Hubungan Onset Stemi dan Door to ECG dengan System Delay Pasien Stemi di Ruang IGD: The Relationship Between STEMI Onset and Door-to-ECG Time with System Delay in STEMI Patients in the Emergency Department - Hanafiah, Yusuf; Elpriska, Elpriska (Chakra Brahmanda Lentera Institute, 2025)
ST-Elevation Myocardial Infarction (STEMI) is a cardiology emergency that requires prompt and accurate management to prevent mortality and serious complications. One of the main challenges in STEMI management is system delay, which is often influenced by two key factors: onset-to-door time and door-to-ECG time. This study aims to analyze the relationship between STEMI onset and door-to-ECG time with system delay in patients presenting to the Emergency Department (ED). This research was an observational quantitative study with a cross-sectional approach, conducted at H. Adam Malik General Hospital, Medan, during the period of September to December 2022. The sample consisted of 86 STEMI patients selected through total sampling. The independent variables were onset time and door-to-ECG time, while the dependent variable was system delay. Data collection instruments included medical record observation forms and a service time stopwatch. Data were analyzed using the Spearman Rank test with a significance level of <0.05. The results showed that 69.8% of patients experienced system delay (≥90 minutes). Most onset times were within the range of 6–10 hours (31.4%), while the fastest door-to-ECG time occurred within 0–3 minutes (44.2%). Statistical tests indicated that both onset time and door-to-ECG time were significantly associated with system delay, with p-values of 0.008 and 0.007, respectively. It can be concluded that the longer the STEMI onset and the slower the ECG is performed after the patient arrives at the ED, the greater the likelihood of system delay. Therefore, public education is necessary to improve early recognition of heart attack symptoms, along with enhanced triage efficiency and rapid ECG protocols in the emergency department.